-113=6(2r-5)+1

Simple and best practice solution for -113=6(2r-5)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -113=6(2r-5)+1 equation:


Simplifying
-113 = 6(2r + -5) + 1

Reorder the terms:
-113 = 6(-5 + 2r) + 1
-113 = (-5 * 6 + 2r * 6) + 1
-113 = (-30 + 12r) + 1

Reorder the terms:
-113 = -30 + 1 + 12r

Combine like terms: -30 + 1 = -29
-113 = -29 + 12r

Solving
-113 = -29 + 12r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-12r' to each side of the equation.
-113 + -12r = -29 + 12r + -12r

Combine like terms: 12r + -12r = 0
-113 + -12r = -29 + 0
-113 + -12r = -29

Add '113' to each side of the equation.
-113 + 113 + -12r = -29 + 113

Combine like terms: -113 + 113 = 0
0 + -12r = -29 + 113
-12r = -29 + 113

Combine like terms: -29 + 113 = 84
-12r = 84

Divide each side by '-12'.
r = -7

Simplifying
r = -7

See similar equations:

| 5+5y+7= | | 3p-2=31 | | -8c+6=1 | | 6X+8+3X-2=-132 | | v+9*3=8 | | -156=-6-5(6+6n) | | -210-5x=-0 | | -5x-6=-2 | | 49s^2=64 | | -8(8-x)=4/5(x-10) | | -1=5+x*6 | | 784=-4x^2+800 | | 800-300= | | P=-30t^2+450t-790 | | -4=r*20-5 | | x^2y^2-x^2= | | 8x+1=4x+3 | | -6(8x+3)-6x=90 | | 0=4+n*5 | | 4b+7= | | 2x+4x+3x+3x=360 | | 5+3n+7=3 | | 4(x-3)=6x+5-3x | | 6(J+3)=102 | | -6m-5(1+3m)=163 | | x+120=24-5x | | 2b+3c=57 | | 15=-4v-v | | -(3n-8)+2=-5(n-3)-(5-4n) | | (6-5)-(2*3-9)+2= | | -31+x=38+4x | | s=7(3.14)zh+2(3.14)z^2 |

Equations solver categories